Inclusion, Contrast and Polysemy in Dictionaries: The Relationship between Theory, Language Use and Lexicographic Practice - Koskela, Anu (Research in Language, 2014)
This paper explores the lexicographic representation of a type of polysemy that arises when the meaning of one lexical item can either include or contrast with the meaning of another, as in the case of dog/bitch, shoe/boot, finger/thumb and animal/bird. A survey of how such pairs are represented in monolingual English dictionaries showed that dictionaries mostly represent as explicitly polysemous those lexical items whose broader and narrower readings are more distinctive and clearly separable in definitional terms. They commonly only represented the broader readings for terms that are in fact frequently used in the narrower reading, as shown by data from the British National Corpus.